A História das Práticas Turísticas no Serviço Social do Comércio de São Paulo (Sesc-SP) - Cheibub, Bernardo Lazary (Revista Rosa dos Ventos - Turismo e Hospitalidade, 2014)
Este trabalho é fruto de uma investigação em fase final de revisão textual, que acontece desde 2011 , acerca da constituição do Turismo no Sesc-SP, examinando as circunstâncias em que a atividade torna-se relevante nas suas políticas. Procurou-se entender as metamorfoses e readequações que nortearam as práticas, diretrizes, posturas e intenções da instituição. A metodologia privilegiada na pesquisa foi a história oral temática, no intuito de fazer o registro da história do envolvimento de profissionais com o Turismo Sesc-SP. Foram realizadas vinte e duas entrevistas com (ex)profissionais e visitas à Biblioteca do Sesc Nacional (DN) e ao setor de Memória e Documentação do Sesc-SP, lugares que congregam documentos importantes relacionados à história do Turismo, na instituição. O recorte cronológico abarca desde os primeiros passos do Sesc-SP com o Turismo, sobretudo à partir de 1979 - ano em que o regional passa a desenvolver excursões, passeios e viagens com maior frequência e tenta se aprofundar conceitualmente do turismo social ao se aproximar de órgãos internacionais de relevância política na área - até 2013, ano no qual termino a pesquisa de campo e as entrevistas. The History of Tourism Practices at Social Service of Commerce in São Paulo (Sesc-SP) - This article is a result of an investigation in final stage of textual review, which happens since 2011 - held on the Doctorate in History, Politics and Cultural Goods of Getulio Vargas Foundation, directed by Professor Bianca Freire-Medeiros - regarding the constitution of tourism at Sesc-SP, examining the circumstances in which tourism become relevant to its policies. We try to comprehend the changes and readjustments that guided the institution’s actions, guidelines, postures and intentions. The methodology privileged in the research was the thematic oral history, in order to make the historiographical record of professionals involved with tourism at Sesc-SP. Twenty two interviews with (former) professionals were performed and were made some visits to the library of Sesc-DN (national department) and to the memory and documentation sector of Sesc-SP, places that keep relevant documents related with the history of tourism in institution. The chronological period embraces since the first steps of Sesc-SP with tourism (1948), passing through 1979 - year that the regional administration of São Paulo starts to develop excursions, tours and travel more frequently and attempts a conceptual deepening on social tourism, approaching from international bodies of political relevance in the area – to the actions taken in 2013, when the field reserarch and the interviews were finished.